Internalization of Islamic Values in the Economic Development of Pesantren - Firman Ashari; Ruslan (al-Afkar, Journal For Islamic Studies, 2026)
Values such as honesty, trust, justice, ukhuwah and social concern are basic principles that should color economic activities in the pesantren environment. However, in practice, the internalization of these values often faces various obstacles, ranging from weak value-based managerial systems, low human resource capacity, to challenges from modernization flows and increasingly complex economic competition. This study uses a qualitative approach with data collection methods that include interviews, observations, and documentation. The subjects in this study came from the Al-Amien Prenduan Economic and Facilities Bureau, the Chairman of the Al-Amien Prenduan Kopontren, the Secretary and Treasurer. The data validity verification methods applied in this study are source triangulation and technique triangulation. The process of internalizing Islamic values in the Al-Amien Prenduan Kopontren is the main foundation in building a religious and sustainable pesantren economy through the cultivation of morals, character, responsibility, Islamic education and discipline. Despite being faced with challenges such as maintaining the consistency of Islamic values in business practices as well as limited capital and infrastructure, Kopontren still shows a strong commitment to upholding sharia business ethics and continues to strive to make improvements in order to maintain the competitiveness and sustainability of its business.